THE LOCAL GOVERNMENT POLICY STRATEGY IN TOURISM DEVELOPMENT IN NORTH GALESONG, TAKALAR REGENCY - Nunu Febriana; Inayah Mutmainnah; Yudhi Andrew Pratama Leomindong (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to identify the local government’s policy strategy in developing tourism in North Galesong, Takalar Regency. The research uses a qualitative method, with data collected through observation, interviews, and documentation. The informants in this study consist of five individuals with different occupational backgrounds. The findings show that: (1) The local government’s strategy for developing tourism in North Galesong focuses on infrastructure development, digital promotion, and community empowerment through Pokdarwis (Tourism Awareness Group) training. Although there are still challenges such as limited facilities, insufficient promotion, and uneven mentoring, this strategy demonstrates the government’s commitment to achieving sustainable tourism. However, more systematic planning, technological support, and active community participation are needed to enhance tourism attractiveness. (2) The process of formulating the tourism development strategy begins with identifying obstacles such as limited funding and human resources, which are addressed through collaboration among the government, community, academics, and private sector. Strategic priorities are determined by considering economic factors, local culture, and environmental sustainability. Furthermore, the community is empowered through Pokdarwis and supported by village funds, culminating in the implementation of a pentahelix collaboration model to ensure that the strategy is well-directed, participatory, and sustainable.